α-glucosidase and 15-lipoxygenase inhibitory activities of phytochemicals from calophyllum symingtonianum - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher; Mohamed Zulkifli, Razauden (Natural Product Inc., 2015)
A phytochemical investigation of the crude extracts of the bark and leaves of Calophyllum symingtonianum has resulted in the isolation of inophyllum D, inophyllum H, calanone, isocordato-oblongic acid, amentoflavone, carpachromene and lupenone. Their chemical structures were elucidated and confirmed by spectroscopic analysis. All flavonoids and coumarins showed significant α-glucosidase inhibitory activity, while amentoflavone gave a positive result against 15-lipoxygenase inhibition.